Studies on the Cultivation of Innovation Ability of Chinese College Students Majoring in Mathematics - Yang, Zezhong; Wang, Ting (American Journal of Creative Education, 2020)
To obtain more innovative personnel, the outline of the national program for medium and long term education reform and development in China calls for the reform of the training systems to find new models and explore new methods. Therefore, a series of related researches have been conducted on it in the field of mathematics teaching in college and university in recent years. By using the literature analysis method, through collecting, identifying and sorting out the research on the cultivation of innovation ability of college students majoring in mathematics in recent 10 years, this study summarizes the current situation and strategies of the cultivation. The results showed that the current research mainly focused on the situation and the cultivation strategy. As for the current situation of the cultivation of innovation ability of students majoring in mathematics, the researchers think that the current college curriculum is unreasonable, the cultivation method is not scientific, the practical teaching system is not perfect, the students' consciousness is weak, lacking of the specialized teachers and the evaluation mechanism is not perfect. As for how to cultivate the innovative ability of students majoring in mathematics, the current researchers suggest that we should change the educational concept, optimize the curriculum structure, carry out practical teaching reform, cultivate excellent teachers and build a reasonable evaluation mechanism. Overall, the current research is still relatively scattered, there are many gaps. Therefore, it is suggested that future studies should be conducted in a comprehensive and systematic manner.